The Geographical Distribution for The Central Directions and The Intensity of Rural Areas of Rwandz District. (Raparin Journal of Humanities (RJH), 2026)
The key topics in geographical sciences are the distribution patterns and direction of population concentration, which illustrate the relationship between land and population. Particularly, the study of rural settlement populations is more significant, whereas the relationship between population and land is more clearly defined in these areas.This study aims to assess the trends in population distribution in Rawanduz District's Rural Settlements. It uses Geographic Information Systems (GIS) to explore present settlement patterns. The quantitative method has been used in this study to analyze and measure the spatial distribution of population concentration, rural settlements, density, and central locations. Exploring rural settlements by this scientific approach lays the groundwork for future rural settlements.This study aims to map and explore the central points of rural settlement distribution in the area of the study. At the same time, it increases the village's comprehension of settlement patterns. The study first examined the distribution patterns in Rawanduz District's Rural Settlements to achieve this aim. The study then used statistics (quantitative method), and GIS tools (namely ArcGIS Pro 3.1), including spatial statistical tools to analyze the central directions, and extracting central points and nearest neighbors, as well as Spatial analysis tools with Interpolation (IDW) function to explore population density and attraction areas.